Penerapan Algoritma K-Means Dalam Pengelompokan Penerimaan Imunisasi Dasar Lengkap Menurut Provinsi - Rico Hermanto Manurung; Muhammad Ridwan Lubis; S Saifullah (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2021)
Immunization is a form of immune system or immune to disease. The process of giving immunizations gives the body immunity to be immune to disease. With routine immunization improves the quality of children's health. According to data from the official Government website, the lowest percentage of children aged from 12 to 23 months who received immunization is 40% at the provincial level in Indonesia. This research was conducted by grouping the minimum level of immunization from 2015 to 2018 using the K-means method. The data obtained are grouped into 2 Clusters starting from the lowest and highest. The author obtains data from the official website of Government which addresses https://bps.go.id. The conclusion of this study concludes that there is still a lack of child immunization in Indonesia, so that there is an expectation that the Government in every region in Indonesia be more active for the welfare of children's health.